Optimization Design of Train-mounted Cabinet Based on FEM Simulation - ZHANG Chenlin; DING Jie; ZHU Mingjie; HU Changfa; ZENG Yunfeng (Kongzhi Yu Xinxi Jishu)
It put forward an optimal integrated design method for train-mounted cabinet, whose basic principle is using the structure simulation model. The pointer algorithm is used to find the optimal solution by integrating Abaqus to carry on the static strength and model simulation in Isight, and random vibration fatigue simulation is used to verify this optimized scheme. An optimized train-mounted cabinet successfully lost weight of 11.5% , which shows that the method can effectively realize lightweight design of cabinets.